2011
DOI: 10.1074/jbc.m110.165704
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor-Retinoid X Receptor (LXR-RXR) Heterodimer Cistrome Reveals Coordination of LXR and AP1 Signaling in Keratinocytes

Abstract: Liver X receptors (LXRs) play a critical role in regulating lipid synthesis and transport in numerous tissues. In the skin, activation of LXR induces keratinocyte differentiation and improves epidermal permeability barrier homeostasis. To elucidate the mechanism of LXR action in skin, we mapped its cistrome by identifying LXR␤-RXR␣ binding sites using ChIP-on-chip in normal human epidermal keratinocytes (NHEKs). The cistrome was integrated with transcription data to obtain a global view of LXR action in kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…This fits with the observations of the two presently published mouse LXR ChIP-Seq studies, where only 6.3% [18] or up to 8% [19] of the LXR peaks contained a DR4-type RE. In a very recent ChIP-on-chip report, 2035 LXRβ-RXR binding sites were identified within promoter regions of normal human epidermal keratinocytes [40]. Although 1666 (82%) of these rather large genomic fragments contain a kind of DR4-type RE, only 142 (7.0%) of them are highly scored, resulting in a very similar percentage as in our human and the mouse ChIP-Seq studies.…”
Section: Discussionsupporting
confidence: 73%
“…This fits with the observations of the two presently published mouse LXR ChIP-Seq studies, where only 6.3% [18] or up to 8% [19] of the LXR peaks contained a DR4-type RE. In a very recent ChIP-on-chip report, 2035 LXRβ-RXR binding sites were identified within promoter regions of normal human epidermal keratinocytes [40]. Although 1666 (82%) of these rather large genomic fragments contain a kind of DR4-type RE, only 142 (7.0%) of them are highly scored, resulting in a very similar percentage as in our human and the mouse ChIP-Seq studies.…”
Section: Discussionsupporting
confidence: 73%
“…This cross-talk was also observed in the LXRE present in the promoters of LXR target genes such as ABCA1, ABCG1, and LXRα itself. A previous genome-wide cistrome analysis revealed an enrichment of AP1 motifs at a location adjacent to the LXR-RXR heterodimer binding sites13. Consistently, we found that the LXRE located in the promoter of LXRα or ABCA1 overlapped with an AP1 motif, 5′-TGACCAG-3′ or 5′-TGACCGA-3′, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, our results showed that formation of a LXRα/RXRα heterodimer and binding of LXRα to LXE of the abca1 promoter were reduced by high glucose, even though high glucose increased RXRα expression. It has been well documented that activated LXR stimulates formation of a heterodimer with RXR and controls transcriptional activity of the abca1 gene6263. Indeed, Repa et al .…”
Section: Discussionmentioning
confidence: 99%